1993
DOI: 10.1159/000110299
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the International Headache Society Criteria for Migraine

Abstract: For general practitioners and in epidemiological studies, migraine poses diagnostic problems. It is a polymorphous disease, with diagnosis based on a subjective description of symptoms. The International Headache Society (IHS) proposed a set of rigorous criteria for the diagnosis of migraine. We studied its validity on 171 outpatients of headache clinics and on 96 headache sufferers detected during an annual checkup for workers. The criteria showed an excellent specificity, however sensitivity in both samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 7 publications
2
41
0
Order By: Relevance
“…12,13 Although overall prevalence, age and sex distribution, and frequency * These data are presented for the subpopulation of subjects who had taken medication to treat their last attack. and duration of migraine attacks are comparable to what they were 10 years ago, 4 there may have been a change in perceived pain intensity. In 1989, 74% of subjects reported severe or very severe pain, whereas in the current study this proportion has fallen to 62.5%.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…12,13 Although overall prevalence, age and sex distribution, and frequency * These data are presented for the subpopulation of subjects who had taken medication to treat their last attack. and duration of migraine attacks are comparable to what they were 10 years ago, 4 there may have been a change in perceived pain intensity. In 1989, 74% of subjects reported severe or very severe pain, whereas in the current study this proportion has fallen to 62.5%.…”
Section: Resultsmentioning
confidence: 74%
“…Using the algorithm described in our 1990 study, the diagnostic accuracy of the combined migraine (IHS categories 1.1 and 1.2) and borderline migraine groups (which is more restrictive than IHS criterion 1.7) was validated against clinical diagnosis of migraine by French neurologists. 4 It was found that the sensitivity of diagnosis was 95%, but that specificity was reduced from 91.9 to 78.4% compared with IHS criteria 1.1 and 1.2. However, using identical diagnostic criteria, the prevalence of migraine in France appears to have been stable over the past 10 years.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The IHS does not consider CRS a valid cause of facial pain or headache, yet many cases of "sinus headache" are thought to represent undiagnosed migraine because they satisfy IHS criteria [12•]. Multiple studies have cast doubt as to the validity of using IHS criteria as a gold standard to diagnose migraine, rather than physician evaluation [13][14][15]. In fact, many nonmigraine episodes (eg, head trauma) can qualify for at least a migrainous episode per IHS criteria until actual physician assessment is made [16•].…”
Section: Discussionmentioning
confidence: 99%